Use of Social Media by Online Newspapers in Saudi Arabia - Hussain, Akhtar; Ahmad, Parvez (DESIDOC Journal of Library & Information Technology, 2014)
The purpose of this study is to discuss the use of social media by online newspapers in Saudi Arabia.The websites of online newspapers in Saudi Arabia were surveyed and the social media tools available on their websites were studied. Total 42 online newspapers’ websites were analysed, out of which 36 Arabic online newspapers have implemented web 2.0 applications. In Arabic 3 newspapers also have English version, in addition 2 more newspapers were in English only. Further, 4 websites were not working. The findings of this study can be utilised to assess the status of assorted web 2.0 tools used in online newspapers. It may enable future research to investigate other aspects, such as use of web 2.0 by online newspapers of a particular country and its states. The paper begins with an introduction to Saudi Arabia’s education and media technology, and further attempts to define and explain to web 2.0 applications which are useful to the online newspapers. http://dx.doi.org/10.14429/djlit.34.6747